2001
DOI: 10.1055/s-2001-18122
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Colloid Cysts - Comparison of Endoscopic and Microsurgical Management

Abstract: The management of colloid cyst remains controversial, evaluation of the competing methods seems to be necessary. We report on our experience with colloid cysts in the last decade: ten were managed solely endoscopically, 10 were resected microsurgically (9 via a transcortical/transventricular, 1 via a transcallosal approach). The outcome in the endoscopic group was excellent in 9 cases and unsatisfying in 1 case (recurrence). In the microsurgical group we achieved a good outcome in 5 of 10 cases, a fair outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 8 publications
2
51
1
Order By: Relevance
“…Endoscopic procedures yield satisfactory results, but limited follow up is available for these cases. 12) In our case, no recurrence occurred for 2 years after total removal of the cyst.…”
Section: Ectopic Colloid Cyst Is Difficult To Differentiatementioning
confidence: 79%
“…Endoscopic procedures yield satisfactory results, but limited follow up is available for these cases. 12) In our case, no recurrence occurred for 2 years after total removal of the cyst.…”
Section: Ectopic Colloid Cyst Is Difficult To Differentiatementioning
confidence: 79%
“…However, microsurgical resection is associated with significant morbidity and prolonged post-operative hospital stays. 2,[20][21][22][23][24][25][26][27][28] More recently, some authors have reported less invasive microsurgical techniques with endoscopic assistance, 22 neuronavigation 29 and approaches through cylindrical retractors using stereotactic frames. 30,31 Although potentially less invasive, stereotactic aspiration is associated with recurrence rates of 30-80% [32][33][34] with recurrences occurring as early as two months in half of these.…”
mentioning
confidence: 99%
“…15,20,28,32 Several series of patients affected by third ventricle colloid cysts have reported an average rate of recurrence higher in cases in which the cyst wall was partially resected compared with those in which the capsule was entirely removed (6.87% vs 0.71%, respectively). 2,4,5,9,[14][15][16]20,21,23,29,31,32 Based on these data, we attempted to achieve a complete resection of the colloid cyst in all patients. However, the endoscopic approach to the third ventricle, usually performed through the foramen of Monro, does not provide an adequate view of the cyst's attachment to the tela choroidea, necessitating that the cyst capsule be stripped away from the roof of the third ventricle in a "blinded" fashion, especially when attachment of the lesion is very posterior.…”
Section: Discussionmentioning
confidence: 99%
“…2,15,20,24,26,29 The rate of recurrence varies among the different series, ranging from 0% to 11.47%. 2,4,5,9,[14][15][16]18,20,21,23,26,29,31,32 Complete resection of third ventricle colloid cysts, including their attachment to the tela choroidea, is important to reduce the risk of recurrence. However, stripping away the cyst wall from its insertion in the roof of the third ventricle may result in severe hemorrhage if the internal cerebral veins are injured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation